Effectiveness of recruitment to a smartphone-delivered nutrition intervention in New Zealand: analysis of a randomised controlled trial. Issue 6 (2nd July 2017) - Volkova, Ekaterina; Michie, Jo; Corrigan, Callie; Sundborn, Gerhard; Eyles, Helen; Jiang, Yannan; Mhurchu, Cliona Ni
Abstract : Objectives: Delivery of interventions via smartphone is a relatively new initiative in public health, and limited evidence exists regarding optimal strategies for recruitment. We describe the effectiveness of approaches used to recruit participants to a smartphone-enabled nutrition intervention trial. Methods: Internet and social media advertising, mainstream media advertising and research team networks were used to recruit New Zealand adults to a fully automated smartphone-delivered nutrition labelling trial (no face-to-face visits were required). Recruitment of Māori and Pacific participants was a key focus and ethically relevant recruitment materials and approaches were used where possible. The effectiveness of recruitment strategies was evaluated using Google Analytics, monitoring of study website registrations and randomisations, and self-reported participant data. The cost of the various strategies and associations with participant demographics were assessed. Results: Over a period of 13 months, there were 2448 registrations on the study website, and 1357 eligible individuals were randomised into the study (55%). Facebook campaigns were the most successful recruitment strategy overall (43% of all randomised participants) and for all ethnic groups (Māori 44%, Pacific 44% and other 43%). Significant associations were observed between recruitment strategy and age (p<0.001), household size (p<0.001), ethnicity (p<0.001), gender (p=0.005) and interest in healthy eating (p=0.022). Facebook campaigns resulted in the highest absolute numbers of study registrations and randomisations (966 and 584, respectively). Network strategies and Facebook campaigns cost least per randomised participant (NZ4 and NZ5, respectively), whereas radio advertising costs most (NZ179 per participant). Conclusion: Internet and social media advertising were the most effective and least costly approaches to recruiting participants to a smartphone-delivered trial. These approaches also reached diverse ethnic groups. However, more culturally appropriate recruitment strategies are likely to be necessary in studies where large numbers of participants from specific ethnic groups are sought. Trial registration: ACTRN12614000644662; Post-results.